2008
DOI: 10.1620/tjem.214.303
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Insulin-Like Growth Factor-II Receptor in Reactive Astrocytes in the Spinal Cord of Amyotrophic Lateral Sclerosis Transgenic Rats

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease caused by selective motor neuron death. We developed a rat model of ALS expressing a human cytosolic copper-zinc superoxide dismutase (SOD1) transgene with two ALS-associated mutations: glycine to alanine at position 93 (G93A) and histidine to arginine at position 46 (H46R). Although the mechanism of ALS is still unclear, there are many hypotheses concerning its cause, including loss of neurotrophic support to motor neurons. Recent eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…The microglia, on the other hand, did not express IGF-II/M6P receptors either in control or in kainic acid-treated rats. This observation is consistent with some earlier results which showed a disparity in the localization of the lysosomal enzymes and the receptor in glial cells following injury or pathological conditions (German et al, 2002;Nakanishi, 2003;Hawkes et al, 2006;Dagvajantsan et al, 2008;Amritraj et al, 2009). Since lysosomal enzymes can partly be transported by cation-dependent-M6P as well as sortilin receptors (Hawkes and Kar, 2004;Braulke and Bonifacino, 2009), it is possible that trafficking of cathepsins in reactive microglia may be mediated by these receptors rather than the IGF-II/M6P receptor.…”
Section: Discussionsupporting
confidence: 92%
“…The microglia, on the other hand, did not express IGF-II/M6P receptors either in control or in kainic acid-treated rats. This observation is consistent with some earlier results which showed a disparity in the localization of the lysosomal enzymes and the receptor in glial cells following injury or pathological conditions (German et al, 2002;Nakanishi, 2003;Hawkes et al, 2006;Dagvajantsan et al, 2008;Amritraj et al, 2009). Since lysosomal enzymes can partly be transported by cation-dependent-M6P as well as sortilin receptors (Hawkes and Kar, 2004;Braulke and Bonifacino, 2009), it is possible that trafficking of cathepsins in reactive microglia may be mediated by these receptors rather than the IGF-II/M6P receptor.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that we were unable to capture microgliosis if it occurred at an intermediate timepoint between those examined in our study. While astrogliosis has been associated with various neurocognitive disorders (De Keyser et al 2008), a number of studies show a possible protective role of reactive astroglia in CNS injuries (Myer et al 2006;Faulkner et al 2004;Dagvajantsan et al 2008). Our observation of astrogliosis only suggests an association between GW agent-induced astrogliosis and behavioral changes.…”
Section: Discussionmentioning
confidence: 52%
“…This observation is consistent with some earlier results that showed a disparity in the localization of the lysosomal enzymes and the receptor in glial cells after injury or pathological condi-tions. 16,33,46,67,68 Because certain lysosomal enzymes can be transported via a cation-dependent M6P receptor in selected cells, 22,69 it is possible that cathepsins in reactive microglia may be transported by a cation-dependent M6P receptor rather than the IGF-II/M6P receptor. Earlier studies using cultured cells have shown that U18666A treatment or siRNA-mediated NPC1 depletion, can redistribute IGF-II/M6P receptors to cholesterolladen endosomes and impair receptor recycling from late endosomes to the trans-Golgi network.…”
Section: Discussionmentioning
confidence: 99%